Methods of Solving the Problem of Disruptive Behavior According to Some Variable "A Field Study on a sample of classroom teachers in the City of Jableh"s - كحيلة, ريم (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research aimed to study the differences in the methods of solving the problem of disruptive behavior on a sample of classroom teachers in the city of Jableh according to the following variables: (gender, years of experience, educational qualification). The research sample consisted of (179) male and female classroom teachers in the city of Jableh. The researcher used the descriptive method, and used "The Methods of Solving the Problem of Disruptive Behavior Questionnaire" of "Radwan (2022)".The results showed that there is no statistically significant difference between the study sample in the methods of solving the problem of disruptive behavior according to gender variable, while there are statistically significant differences between the means of their scores on the methods of (moderate inhibition, counseling and persuasion, involvement in activities, building human relationships) according to the number of years of experience in favor of teachers with less than 5 years of experience, and according to the educational qualification variable for teachers who obtained a master’s degree or doctorate in child education. There are also statistically significant differences between their average scores on the methods of (physical punishment and moral punishment) according to the number of years of experience in favor of teachers with more than 10 years of experience, and according to the educational qualification variable in favor of teachers who obtained a bachelor's degree in education only.